THE CORRELATION BETWEEN STUDENTS’ READING INTEREST AND TRANSLATION ABILITY AT THE SECOND GRADE IN SMPN 4 TOLITOLI - Ismail Yunus (Jurnal Madako Education, 2022)
The aim of this research is to find out the correlation between students’ reading interest and translation ability in second grade at SMP Negeri 4 Tolitoli. This is a quantitative research design. There were 32 students as sample of this research. The samples were selected purposively. Test and questionnaire used to collect data. The data collected were analyzed statistically. The result of this research indicated that the correlation coefficient value is 0,551 which indicates that there a positive moderate correlation. value significant (2- tailed) is 0,001, which means that there is a significant correlation between students’ reading interest and translation ability because the value is 0,001 < 0,05. Then, ha accepted and ho is rejected.